Pengaruh Penggunaan Model Cooperative Learning Tipe Cooperative Integrated Reading and Composition Terhadap Peningkatan Pemahaman Konsep Peserta Didik - Ria Epina; Uus Manzilatusifa; Sungging Handoko (EDUCARE, 2018)
This research is motivated by the lack of understanding of students' concepts that can be seen when educators give a question to students who cannot repeat the concept with their own language. The purpose of this study was to determine the use of Cooperative Learning learning types of Cooperative Integrated Reading and Composition (performed very well or not, so that if it is good then there will be an influence on increasing students' concept understanding. This research was conducted in the even semester of 2017/2018 school year. The instruments used in this study are observation sheets and test types describing the concept comprehension ability in writing so the data to be collected in this study are pretest and posttest data which are then analyzed by using SPSS 22.0 for Windows software to see the effect of using learning models CIRC. Hypothesis testing results using the observation sheet, and t-test which shows that the CIRC model use model is used very well, and based on the results of statistical tests the understanding of the concept of students in the experimental class experienced a significant increase compared before using it.